Development of automated exhaust fan for modern kitchen with IoT notification system - Samsudin, Adam; Suliaman, Muhammad Syukri; Bahari, Muhamad Falihan; Noor Azhuan, Nur Azura; Hussin, Nor Hafizah; Mohd Yussoff, Nurul Hajar; Rosli, Norhayati; Irianto, Irianto (Semarak Ilmu Publishing, 2024)
This project shows the development of an automated exhaust fan for a modern kitchen with an IoT notification system for a better air ventilation system with lower electrical consumption and cheaper installation costs. Utilizing an exhaust fan as the ventilation system will significantly lower the cost of installation and maintenance. The exhaust fan will carry the process of removing hot air from the kitchen so that cooler surrounding temperatures can be achieved. The application of an automated microcontroller system will allow higher energy efficiency for daily cooking appliance usage. Then, the application of the DHT22 temperature sensor as the input for the microcontroller which can detect the precise temperature of the surrounding air. The exhaust fan will automatically turn ON when it detects the surrounding temperature is increased from 33℃. However, a notification will be sent to the user through the Blynk Application when the temperature of the kitchen is increasing and achieved 37℃ while a buzzer will turn ON to alert people in the house. Next, the AC voltage controller will help regulate the speed of the fan according to the input temperature so that more energy can be saved during long daily usage. At the end of this project, the outcome product will become a microcontroller that can be used in various types of households that already have a wall-mounted exhaust fan. Moreover, more users will be able to install this whole ventilation system for their hot kitchen due to low installation and maintenance costs. Lastly, the electrical monthly bill can be reduced.